Recycling of asphalt pavements with asphalt rubber - Pais, Jorge C. (2008)
Pavement recycling has been an important rehabilitation technique to deal with reclaimed materials from old pavements which are usually sent to landfills. The application of this technique contributes to: i) the accomplishment of the requirements defined by the European legislation for the amount of material sent to landfills; ii) the reduction in the use of new raw materials used to produce pavement layers. The reduction of materials to be used in pavement rehabilitation has also been possible through the use of asphalt rubber binder (i.e. asphalt modified by crumb rubber from ground tyres) in the production of asphalt mixtures. These mixtures, named asphalt rubber mixtures, have shown an excellent performance in pavement rehabilitation in terms of fatigue and reflective cracking. This behaviour is based on the physical properties of the asphalt rubber which are transferred from the rubber to the net asphalt. The use of asphalt rubber in pavement recycling produces a binder which is a blend of the reclaimed mix binder and the new asphalt rubber added to the reclaimed asphalt mix. This recycled binder presents properties mainly based on recycling rates and on the binders used in recycling. The behaviour of the recycled mixture depends on these factors. This paper presents the results of the properties evaluated for recycled mixtures derived from the type of binder presented in the reclaimed asphalt mix and recycling rate. The influence of the reclaimed asphalt mixes and recycling rate was studied to optimize the behaviour of the recycled mixtures. The mechanical performance in terms of stiffness and fatigue resistance was also evaluated for the recycling design process.